2002
DOI: 10.1002/ptr.984
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of serum phosphatases activity in Swiss albino mice against gamma irradiation by Mentha piperita Linn.

Abstract: The modulatory influence of mentha oil (Mentha piperita Linn.) against a lethal dose (8.0 Gy) of gamma irradiation on the activities of serum phosphatases in Swiss albino mice was studied at various post-irradiation intervals between 6 h and 30 days. Mentha oil (40 microL/animal/day) given orally for 3 consecutive days prior to whole-body irradiation (8.0 Gy) showed a modulation of activity of serum phosphatases. The values of acid phosphatase activities were significantly higher in the irradiated groups throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…Recently, another species of mint (Mentha piperta) has been reported to inhibit the radiation-induced elevation in the alkaline and acid phosphatases [34]. Similarly, other plant extracts like Ocimum sanctum [8,9,17], Panax ginseng [57], Spirulina platensis [27], Chlorella vulgaris [38], garlic [41], Ginkgo biloba [3] and Phyllanthus niruri [48] have been reported to be radioprotective.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another species of mint (Mentha piperta) has been reported to inhibit the radiation-induced elevation in the alkaline and acid phosphatases [34]. Similarly, other plant extracts like Ocimum sanctum [8,9,17], Panax ginseng [57], Spirulina platensis [27], Chlorella vulgaris [38], garlic [41], Ginkgo biloba [3] and Phyllanthus niruri [48] have been reported to be radioprotective.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Mint reduces Serum Phosphatases Studies by Samarth et al, [55,56] have shown that both oil as well as the aqueous extract of M. piperita modulated levels of serum phosphatases at different assay time points (6 h and 30 days post-irradiation). Exposure of Swiss albino mice to lethal dose of γ irradiation (8.0 Gy) caused a marked increase in the activities of serum phosphatases and acid phosphatase.…”
Section: Mint Increases Levels Of Antioxidant Enzymesmentioning
confidence: 99%
“…Many synthetic as well as natural agents have the efficacy as a protector against radiation injuries (Nair et al 2001). Plant extracts such as Mentha (Samarth et al 2002) have been found to have radioprotective effects in mammals. Mentha piperita (Linn.…”
Section: Introductionmentioning
confidence: 99%